- KENDALA DAN UPAYA GURU PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DALAM MENUMBUHKEMBANGKAN SIKAP MODERAT SISWA DI SD SARASWATI 6 DENPASAR: - - I Dewa Gede Darma Permana; I Nyoman Kiriana; Ni Komang Sutriyanti (UHN IGB Sugriwa Denpasar, 2023)
Intolerant attitude is a challenge for an environment that has heterogeneous patterns in it. As happened in Indonesia, where historically there have been several cases of intolerance that even targeted the world of education precisely in schools. On this basis, it is important for teachers to make efforts in developing moderate attitudes in students from an early age, as done by Hindu Religious Education and Ethics teachers at SD Saraswati 6 Denpasar. However, in this effort, it is known that there are several obstacles faced by teachers. Reflecting on this, this study is interested in identifying the obstacles and efforts of Hindu Religious Education and Ethics teachers in developing moderate attitudes of students at Saraswati 6 Denpasar Elementary School. In this study, several problems are formulated, namely related to the obstacles faced by teachers and teachers' efforts to overcome the obstacles being faced. The research method in this paper uses a type of qualitative research with a descriptive naturalistic approach, primary and secondary data sources, the technique of determining informants is purposive sampling, data collection methods that use observation techniques, interviews, document recording, and literature studies, and using data analysis from Miles and Huberman. The results of this study indicate that some of the obstacles faced during online learning are obstacles in terms of teaching materials, learning methods, assessment tools, and time allocation. The results of this paper are expected to be a guide for Hindu Religious Education and Ethics teachers and other teachers to know the obstacles and efforts that can be made to develop moderate attitudes in students.